Criminal Liability of the Perpetrator of Fraud in Money Transfers Using Counterfeit Money: A Study Of Decision No. 340/PID.B/2024/PN.SMG - Muhammad Rifqi; Aang Asari (Program magister Kenotariatan Fakultas Hukum Universitas Lambung Mangkurat, 2026)
This study was based on the emergence of a new fraud modus operandi in cash on delivery (COD) transactions through the use of modified counterfeit money that resembles genuine money, as occurred in Decision Number. 340/Pid.B/2024/PN.Smg. This phenomenon not only causes material losses to victims, but also threatens public trust in the cash payment system in the era of digital transactions. This study purposes to analyze the criminal liability of the perpetrator, assess the accuracy of the prosecutor's accusation in the use of Article 378 of the Criminal Code (KUHP) and examine the possibility of the application from Article 34 paragraph (2) of the Currency Law against the actions of the perpetrator who spread counterfeit money. The research method applied is a normative legal approach with a case study, supported by qualitative analysis through judicial decisions, literature, regulations, and interviews. The findings reveal that all elements of Article 378 of the Criminal Code were proven to have been fulfilled, starting from the deception in the form of purchasing and modifying counterfeit money, a series of deceptions such as pretending to withdraw money from an ATM, and the success of the perpetrator in persuading the victim to hand over an iPhone 12.